Independence, Work Ethic, Spirituality, and Productivity: A Comparative Study of Several Asian Countries - Mustofa Mustofa; Suyanto Suyanto; Bambang Suprayitno; Nita Kusumawardani (Journal of Social Science, 2022)
This study compares the values ??of independence, work ethic, spirituality, and productivity in several Asian countries. The other purpose of this study is to determine the effect of independence, work ethic, and spirituality on productivity. This study uses World Value Survey (WVS) data with the criteria of respondents who answered the WVS wave 7 questionnaires from Asian countries with a sample size of 19,795. The quantitative research method uses descriptive analysis techniques and probit regression analysis. The descriptive analysis technique uses crosstab, while the probit regression analysis technique is used to determine the effect of independence, work ethic, and spirituality on productivity in several Asian countries. Analysis crosstab shows that Tajikistan, Iran, Taiwan, Pakistan, and the Philippines have a high proportion of unemployed. Kyrgyzstan, Jordan, China, Bangladesh, and Vietnam have a higher tendency for freedom of choice (independence) in their respective country groups. Kyrgyzstan, Jordan, China, Pakistan, and Myanmar have higher work ethic tendencies. Russia, China, Japan, and Vietnam have minor religious inclinations. Probit regression results prove that independence, work ethic, and spirituality significantly affect the dependent variable (productivity). Independence and work ethic have a positive influence, while spirituality has a negative influence. In contrast, all members of the West Asian group all countries have important religious inclinations.